Dielectric relaxation and phase transitions at cryogenic temperatures in 0.65 [Pb (Ni13 Nb23) O3] -0.35PbTi O3 ceramics - Singh S.P.; Singh A.K.; Pandey D.; Yusuf S.M. (My University, 2025)
Dielectric measurements on 0.65 [Pb (Ni13 Nb23) O3] -0.35PbTi O3 ceramic in the temperature range 90-470 K show a relaxor ferroelectric transition around 350 K with a Vogel-Fulcher freezing temperature of 338 K and an appearance of a nonergodic relaxor ferroelectric phase of tetragonal structure at room temperature. This nonergodic phase reenters into the relaxor state at low temperatures as evidenced by the appearance of a frequency dependent anomaly in the imaginary part of the dielectric constant around 160 K, similar to those reported in other relaxor ferroelectric based morphotropic phase boundary ceramics. The polarization relaxation time for the 160 K anomaly also follows Vogel-Fulcher type temperature dependence. Temperature dependent magnetization measurements show that this low temperature anomaly is not linked with any magnetic transition. Elastic modulus and low temperature x-ray diffraction measurements reveal a tetragonal to monoclinic phase transition around 225 K. It is argued that the low temperature dielectric dispersion around 160 K results from the freezing of mesoscopic conformally miniaturized monoclinic domains formed inside the parent tetragonal domains below the structural phase transition temperature of 225 K. © 2007 The American Physical Society.